Synthesis of activity evaluation of flavonoid derivatives as ɑ-glucosidase inhibitors - Zhu, Hua; Zhong, Xin (Frontiers in Chemistry, 2022)
Six flavonoid derivatives were synthesized and tested for anti-α-glucosidase activities. All derivatives were confirmed using NMR and HRMS and exhibited excellent inhibitory effects on α-glucosidase. Derivative 4 exhibited the highest anti-α-glucosidase activity (IC50: 15.71 ± 0.21 μM). Inhibitory mechnism and inhibition kinetics results showed derivative 4 was a reversible and mixed-type inhibitor. Molecular docking revealed that derivative 4 was tightly bind to the amino acid residues of active pocket of α-glucosidase. This results also showed that the hybridization of flavonoid and phenylpropionic acid would be a useful strategy for the development of α-glucosidase inhibitors.